A Pilot Study of Technology Adoption: An Analysis of Consumers’ Preference on Future Online Grocery Service - Aprianingsih, Atik; Nurfatiasari, Safrani (School of Business and Management Institut Teknologi Bandung, 2017)
Abstract. The huge number of smartphone users in Indonesia is the main reason that most of new online retailers choose to develop mobile application-market based grocery. However, online grocery goes through sluggish rate of development due to minimum level on adoption of technology by consumers. The most barriers in adopting this technology are difficulties in transaction, late deliveries, incomplete information, and difficulties with site navigation and complex procedure also security in money transaction. Through literature review, this study attempts to go further to elaborate mobile application online grocery features that can be applied to promote an increasing online grocery service adoption. Based on the finding, the best combination features which more likely support customers to perceived convenience in using online grocery service is mobile application that contain nutritional quality information, allows customers to search the product by its attribute, provide order status tracker that allows customers to trace their groceries and provide cash on delivery service as payment method. Keywords: Online grocery service, mobile application features, technology adoption,